Effect of Silver Black Plastic Mulch and Organic Fertilizer Dosage on Plant Chlorophyll Growth and Content Cayenne Pepper (Capsicum annum L.) - Gifridus, Valeria; Sedijani, Prapti; Raksun, Ahmad (Jurnal Biologi Tropis, 2024)
Cayenne pepper is one of the leading horticultural products in the agricultural sector in Indonesia. In order for plants to grow optimally and produce well, it is necessary to apply silver black plastic mulch and a dose of organic fertilizer. This study aims to determine the growth and chlorophyll content of cayenne pepper plants using black silver plastic mulch and doses of organic fertilizer. The study used a randomized block design with 8 treatment combinations and 3 repetitions. The arrangement of treatments was as follows: M0P0: without mulch + 0 kg/m2, M0P1: without mulch+ 1 kg/m2, M0P2: without mulch+ 1.5 kg/m2, M0P3: without mulch+ 2 kg/m2, M1P0: MPHP + 0 kg /m2, M1P1: MPHP + 1 kg/m2, M1P2: MPHP + 1.5 kg/m2, M1P3: MPHP + 2 kg/m2. The results on plant height and leaf number observations on days 28 and 40 showed that the silver black plastic mulch factor make a real impact. Organic fertilizer significantly affected leaf length on day 40, while the interaction of silver black plastic mulch and dose of organic fertilizer affected leaf length and leaf area on day 40. The best combination in this study was black silver plastic mulch and a dose of 1.5 kg organic fertilizer/m2.